Frequent low-impact exposure to THC during adolescence causes persistent sexually dimorphic alterations in the response to viral infection in mice - Hye-Lim Lee; Erica Squire; Yannick Fotio; Alex Mabou Tagne; Jungyeon Lee; John Jeongwoo Yoon; Yedam Hong; Laura Hyunseo Kim; Kwang-Mook Jung; Daniele Piomelli (Elsevier, 2024)
Adolescent exposure to Δ9-tetrahydrocannabinol (THC) has enduring effects on energy metabolism and immune function. Prior work showed that daily administration of a low-impact dose of THC (5 mg/kg, intraperitoneal) during adolescence alters transcription in adult microglia and disrupts their response to bacterial endotoxin or social stress. To explore the lasting impact of adolescent THC exposure on the brain's reaction to viral infection, we administered THC (5 mg/kg, intraperitoneal) in male and female mice once daily on postnatal day (PND) 30-43. When the mice reached adulthood (PND 70), we challenged them with the viral mimic, polyinosinic acid:polycytidylic acid [Poly(I:C)], and assessed sickness behavior (motor activity, body temperature) and whole brain gene transcription. Poly(I:C) caused an elevation in body temperature which was lessened by prior THC exposure in female but not male mice. Adolescent THC exposure did not affect the locomotor response to Poly(I:C) in either sex. Transcriptomic analyses showed that Poly(I:C) produced a substantial upregulation of immune-related genes in the brain, which was decreased by THC in females. Additionally, the viral mimic caused a male-selective downregulation in transcription of genes involved in neurodevelopment and synaptic transmission, which was abrogated by adolescent THC treatment. The results indicate that Poly(I:C) produces complex transcriptional alterations in the mouse brain, which are sexually dimorphic and differentially affected by early-life THC exposure. In particular, adolescent THC dampens the brain's antiviral response to Poly(I:C) in female mice and prevents the transcriptional downregulation of neuron-related genes caused by the viral mimic in male mice.